Evaluating the effectiveness of the smartphone app, Drink Less, compared with the NHS alcohol advice webpage, for the reduction of alcohol consumption among hazardous and harmful adult drinkers in the UK at 6‐month follow‐up: protocol for a randomised controlled trial. (26th November 2020) - Garnett, Claire; Oldham, Melissa; Angus, Colin; Beard, Emma; Burton, Robyn; Field, Matt; Greaves, Felix; Hickman, Matthew; Kaner, Eileen; Loebenberg, Gemma; Michie, Susan; Munafò, Marcus; et al.
ABSTRACT: Background and Aims: Digital interventions are effective for reducing alcohol consumption but evidence is limited regarding smartphone apps. Drink Less is a theory‐ and evidence‐informed app to help people reduce their alcohol consumption that has been refined in terms of its content and design for usability across the sociodemographic spectrum. We aim to evaluate the effectiveness and cost‐effectiveness of recommending Drink Less at reducing alcohol consumption compared with usual digital care. Design: Two‐arm individually randomised controlled trial. Setting: Online trial in the United Kingdom (UK). Participants: Hazardous or harmful drinkers (Alcohol Use Disorders Identification Test [AUDIT] score ≥8) aged 18+ who want to drink less alcohol ( n  = 5562). Participants will be recruited from July 2020 to May 2022 using multiple strategies with a focus on remote digital methods. Intervention and comparator: Participants will be randomised to receive either an email recommending that they use Drink Less (intervention) or view the National Health Service (NHS) webpage on alcohol advice (comparator). Measurements: The primary outcome is change in self‐reported weekly alcohol consumption, assessed using the extended AUDIT‐Consumption, between baseline and 6‐month follow‐up. Secondary outcomes include change in self‐reported weekly alcohol consumption assessed at 1‐ and 3‐month follow‐ups, and the proportion of hazardous drinkers; alcohol‐related problems and injury; health‐related quality of life; and use of health services assessed at 6‐month follow‐up. Effectiveness will be examined with adjusted regression models, adjusting for baseline alcohol consumption and using an intention‐to‐treat approach. A mixed‐methods process evaluation will assess engagement, acceptability and mechanism of action. Economic evaluations will be conducted using both a short‐ and longer‐term time horizon. Comments: This study will establish the effectiveness and cost‐effectiveness of the Drink Less app at reducing alcohol consumption among hazardous and harmful adult drinkers and will be the first randomised controlled trial of an alcohol reduction app for the general population in the United Kingdom. This study will inform the decision on whether it is worth investing resources in large‐scale implementation.